-3.1x+7-7.4x=1.5x-6(x-32)

Simple and best practice solution for -3.1x+7-7.4x=1.5x-6(x-32) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3.1x+7-7.4x=1.5x-6(x-32) equation:



-3.1x+7-7.4x=1.5x-6(x-32)
We move all terms to the left:
-3.1x+7-7.4x-(1.5x-6(x-32))=0
We add all the numbers together, and all the variables
-10.5x-(1.5x-6(x-32))+7=0
We calculate terms in parentheses: -(1.5x-6(x-32)), so:
1.5x-6(x-32)
We multiply parentheses
1.5x-6x+192
We add all the numbers together, and all the variables
-4.5x+192
Back to the equation:
-(-4.5x+192)
We get rid of parentheses
-10.5x+4.5x-192+7=0
We add all the numbers together, and all the variables
-6x-185=0
We move all terms containing x to the left, all other terms to the right
-6x=185
x=185/-6
x=-30+5/6

See similar equations:

| 25+x-10=20 | | 7-3+12=x+6 | | 0/3r=2/1 | | –19t−–7t−6t+20t−–11=–15 | | 7x+12x=93 | | (2x-1)-69=90 | | 71+x=76 | | 0=-5x+15 | | 10(x-1)=2(x+15) | | 3x+60=-9x | | x+72+34=90 | | 6x-1)/4-(5-2x)/2=1 | | 7m+11=102 | | 8(v-3)=-72 | | 3x^2-21x=00 | | 2x=8x-24;X= | | x+2x+3x=4+7+1;X= | | 2a-(8a+1)-(a-2)×5=9 | | 0=x²-4 | | 18+p=26 | | 2√x-1=5 | | 8g+15=4g-29 | | 33m=8 | | x(x-8)=-10 | | 5x+15=-6x+14 | | 10z+30=10 | | 11x-2=6x+38 | | x-3/4+1/6=15/12 | | 2x+4=-x-11 | | 150=x+.07x | | 14y+9=5y+81 | | -5x-3(-2x-14)=163 |

Equations solver categories